1974
DOI: 10.1007/bf02533825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light intensity upon lipid composition ofNitzschia closterium (Cylindrotheca fusiformis)

Abstract: Total fatty acid, total sterol, fatty acids of specific lipid classes, and unsaturated fatty acids produced inNitzschia closterium were compared qualitatively and quantitatively as a function of changes in light intensity. Increased levels of total fatty acids were observed in cells grown at high light intensity when compared to cells grown at low light intensity. However, the percentage of unsaturated fatty acid decreased under high light conditions. Fatty acid analysis of triglyceride and 1,3 diglyceride fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 11 publications
2
29
1
1
Order By: Relevance
“…They described increased levels of highly unsaturated acids (w3 or n-3) with increasing light intensity but with hardly any variation of the unsaturated to saturated acids ratio and polyunsaturated to monoenoic plus saturated acids ratio. In an earlier study, based on fatty acid changes of lipid classes (polar, diglycerides, triglycerides, free fatty acids), Orcutt & Patterson (1974) found an increase in polar lipid fatty acids and a decrease in neutral lipid fatty acids at low light inten- general findings that light regime affects essentially membrane chloroplast lipid through changes In the level of 0 3 polyunsaturated fatty acids. The role of long-chain polyunsaturated acids in phytoplankton physiology remains unclear.…”
Section: Discussionmentioning
confidence: 91%
“…They described increased levels of highly unsaturated acids (w3 or n-3) with increasing light intensity but with hardly any variation of the unsaturated to saturated acids ratio and polyunsaturated to monoenoic plus saturated acids ratio. In an earlier study, based on fatty acid changes of lipid classes (polar, diglycerides, triglycerides, free fatty acids), Orcutt & Patterson (1974) found an increase in polar lipid fatty acids and a decrease in neutral lipid fatty acids at low light inten- general findings that light regime affects essentially membrane chloroplast lipid through changes In the level of 0 3 polyunsaturated fatty acids. The role of long-chain polyunsaturated acids in phytoplankton physiology remains unclear.…”
Section: Discussionmentioning
confidence: 91%
“…C14, C16:0 and C16:1x7) (Fabregas et al, 2004). Based upon the algal species/strains examined (Orcutt and Patterson, 1974;Sukenik et al, 1993), it appears, with a few exceptions, that low light favors the formation of PUFAs, which in turn are incorporated into membrane structures. On the other hand, high light alters fatty acid synthesis to produce more of the saturated and mono-unsaturated fatty acids that mainly make up neutral lipids.…”
Section: Light Intensitymentioning
confidence: 99%
“…Typically, low light intensity induces the formation of polar lipids, particularly the membrane polar lipids associated with the chloroplast, whereas high light intensity decreases total polar lipid content with a concomitant increase in the amount of neutral storage lipids, mainly TAGs (Brown et al, 1996;Khotimchenko and Yakovleva, 2005;Napolitano, 1994;Orcutt and Patterson, 1974;Spoehr and Milner, 1949;Sukenik et al, 1989).…”
Section: Light Intensitymentioning
confidence: 99%
“…High light, in general, leads to oxidative damage of PUFA. Numerous studies have suggested that the cellular lipid content and PUFA decrease with increase in light intensity [104][105][106]. Conversely, Nannochloropsis cells under low light conditions were characterized by high lipid content and high proportions of eicosapentaenoic acid (EPA; 5,8,11,14,17-icosapentanoic acid) [26].…”
Section: Lightmentioning
confidence: 99%